Is the subarctic landscape still a carbon sink? Evidence from a detailed catchment balance. Issue 5 (4th March 2016) - Lundin, Erik J.; Klaminder, Jonatan; Giesler, Reiner; Persson, Andreas; Olefeldt, David; Heliasz, Michal; Christensen, Torben R.; Karlsson, Jan
Abstract: Climate warming raises the question whether high‐latitude landscape still function as net carbon (C) sinks. By compiling an integrated C balance for an intensely studied subarctic catchment, we show that this catchment's C balance is not likely to be a strong current sink of C, a commonly held assumption. In fact, it is more plausible (71% probability) that the studied catchment functions as a C source (−11 ± 20 g C m −2  yr −1 ). Analyses of individual fluxes indicate that soil and aquatic C losses offset C sequestering in other landscape components (e.g., peatlands and aboveground forest biomass). Our results stress the importance of fully integrated catchment C balance estimates and highlight the importance of upland soils and their interaction with the aquatic network for the catchment C balance. Key Points: We show that the catchment C balance is not likely to be a strong current sink of C The results stress the importance of fully integrated catchment C balance estimates Future research should focus on the large areas of upland soils and their integration with the aquatic network